The Renin-Angiotensin System: Alamandine is reduced in patients with Idiopathic Pulmonary Fibrosis - Sipriani, Taís Salvi; dos Santos, Robson Augusto Souza; Rigatto, Katya (Journal of Cardiology and Cardiovascular Medicine, 2019)
Idiopathic Pulmonary Fibrosis (IPF) is a chronic and progressive disease without treatment that leads to death. Therefore, to control its progression to pulmonary hypertension is still a challenge. Moreover, there is no study that has investigated the Renin-Angiotensin System in patients with IPF. Objective: Verify the plasma concentrations of Angiotensin I, Angiotensin II (AngII), Angiotensin-(1-7) [Ang- (1-7)] and Alamandine in patients with IPF. Methods: Ten IPF patients, with or without PH, were included, and ten controls matched by sex and age. Quantitative plasma peptide concentrations (PPC) were expressed as mean and standard deviation or median and interquartile range. The Student Newman-Keuls t test was used for parametric data, Mann-Whitney for nonparametric data and, to compare proportions, the Fisher exact test was performed. The associations between clinical variables and the PPC were evaluated by Pearson or Spearman correlation coefficients. A p ≤ 0.05 was considered statistically significant. Results: The Alamandine plasma concentration was significantly (365%) lower in the IPF group and positively associated (r = 0.876) with pulmonary artery pressure (PAP). In addition, only in control group, the forced expiratory volume (FEV1%) was positively associated (p = 0.758) with Ang-(1-7). Conclusion: This study showed, for the first time, that there is a decrease in Alamandine participation in patients with IPF. The ACE-AngII-AT1 axis may be more active in this disease. In addition, our results suggest that Alamandine might be compensating the increase in PAP, as well as the Ang-(1-7) is improving the forced expiratory volume.